Determinants of Innovation Capability and Nexus between Innovation Capability and Performance of SMEs - Khan, Muhammad Kamran; Takrim, Kausar; Haseeb, Muhammad; Khan, Amir (Pakistan Journal of Humanities and Social Sciences, 2023)
Small and medium-sized businesses (SMEs) are essential for the expansion of any economy, and innovation is what ensures their continued success and improved performance. The main objectives of this study are to identify the key factors that influence innovation capability, to ascertain the effect of innovation capability on SMEs' performance, and to examine the role of innovation capability as a mediator between its key determinants and SMEs' performance. Partial least squares structural equation modelling (Smart PLS-SEM) was used in the study to accomplish this purpose, and data from 249 manufacturing SMEs registered at the Hattar Industrialist Association (HIA), Industrial Estate, Khyber Pakhtunkhwa, Pakistan, were used to collect the data. All of the constructs used in the study are valid and trustworthy according to Cronbach's alpha, which measures structural stability. The results show that operational and managerial capabilities are not statistically significant drivers of SMEs' innovation potential, while technological and transactional capabilities are statistically significant predictors of SMEs' innovation capabilities. The results also show that innovative competency has a positive effect on SMEs' success. The study also found that innovation capability plays a statistically significant role in mediating the relationship between technological capabilities and performance as well as the relationship between transactional capacities and performance. But neither the role of innovation capabilities in mediating the link between operational capabilities and performance nor the function of innovation capabilities in mediating the relationship between managerial capabilities and performance are statistically significant. It indicates that in order to improve the performance of SMEs, it is necessary to investigate the attitudes and behaviour of SMEs in order to identify the causes of their lack of management and operational competencies.